Improving assessment in small fiber neuropathy. Issue 3 (September 2015) - Brouwer, Brigitte A.; Bakkers, Mayienne; Hoeijmakers, Janneke G. J.; Faber, Catharina G.; Merkies, Ingemar S. J.
Abstract Interval measures at the impairment level addressing symptoms and at the activity/participation level addressing daily and social restrictions have not been developed for small fiber neuropathy (SFN). We developed an SFN‐specific Rasch‐built overall disability scale (SFN‐RODS©), an activity/participation scale at the interval level. A preliminary SFN‐RODS containing 146 activity/participation items was assessed twice (reliability studies) in 238 patients with SFN. The ordinal‐based 13‐item SFN‐symptoms inventory questionnaire (SFN‐SIQ©) and pain‐visual‐analogue‐scale were also assessed (validity studies). The pre‐SFN‐RODS and SFN‐SIQ data were subjected to the Rasch analyses. The pre‐SFN‐RODS did not meet Rasch model expectations. Based on requirements, such as misfit statistics, differential item functioning, and local dependency, items were systematically removed and model fit improved. Finally, a 32‐item SFN‐RODS© scale was constructed that fulfilled all Rasch requirements, demonstrating acceptable reliability and validity scores. The 13‐item SFN‐SIQ© was successfully transformed to an interval Rasch‐built measure fulfilling model's requirements. In conclusion, the 32‐item SFN‐RODS© is a disease‐specific interval measure suitable for detecting activity limitations and participation restrictions in patients with SFN. The 13‐item SFN‐SIQ© was transformed through Rasch to an interval measure. The use of these scales is recommended in future clinical interventional trials involving patients with SFN.